MORAL DISENGAGEMENT AND UNETHICAL BEHAVIOR: SYSTEMATIC LITERATURE REVIEW - Sulistyowati, Sulistyowati; Ahmar, Nurmala (Universitas Pakuan, 2023)
ABSTRACTThe purpose of this study is to map research topics, research methods, and research subjects from journals determined by researchers, namely moral disengagement and unethical behavior. The journals collected from Google Scholar are 20 from 2008 - 2022. The most widely used method is the questionnaire, while the subjects are students and employees. This research uses the systematic literature review method. Many cases of violation of the code of ethics still occur frequently in Indonesia and various countries, and one of the factors causing it is unethical behavior and Moral disengagement. Moral disengagement and unethical behavior are important concepts in the field of ethics and organizational behavior. Moral disengagement refers to the psychological process by which an individual justifies or removes their guilt for unethical actions. In the context of organizational behavior, it refers to the tendency of individuals to ignore ethical principles when making decisions or performing actions that harm others or the organization.ABSTRAKTujuan penelitian ini yaitu untuk memetakan topik penelitian, metode penelitian, dan subjek penelitian dari jurnal yang ditentukan peneliti yaitu moral disengagement dan unethical behaviour. Jurnal yang terkumpul dari google scholar yaitu sebanyak 20 dari tahun 2008 - 2022. Metode yang paling banyak digunakan adalah kuesioner, sedangkan subjek yaitu student dan karyawan. Penelitian ini menggunakan metode Systematic Literature Review. Banyak kasus pelanggaran kode etik yang masih sering terjadi di Indonesia maupun di berbagai negara, salah satu faktor penyebabnya adalah perilaku tidak etis dan penurunan moral. Penurunan moral dan keputusan yang tidak etis merupakan konsep yang penting dalam bidang etika dan perilaku organisasi. Penurunan moral mengacu pada proses psikologis di mana seseorang membenarkan atau menghilangkan rasa bersalah mereka terhadap tindakan yang tidak etis. Dalam konteks perilaku organisasi, ini mengacu pada kecenderungan individu untuk mengabaikan prinsip-prinsip etis saat mengambil keputusan atau melakukan tindakan yang merugikan orang lain atau organisasi.